PROVIDING CLEAN WATER FOR THE GENERAL PUBLIC IN KORONG PASA LIMAU - Muknizar, Muknizar; Danyl Mallisza; Risal Abu; Dewirman Prima Putra; Ade Setia Wati; Retno Aprilla Hardi; Robi Arianto; Muhammad Afdil; M. Iqbal; Maharani Syabila JR; Viola Aysiah (Ikatan Dosen Menulis, 2024)
Providing clean water is an effort to meet the community’s need for clean water, which is a basic need for the community. Providing clean water is carried out in various ways, such as drinking water supply systems (SPAM), regional drinking water companies (PDAM) and construction of water strage tanks. Water supply clean water is carried out, namely by building a system of water storage tanks for community ablutions. There is also a goal of providing clean water, namely to improve the level of community health. In providing clean water, students have a work program to fulfill the results or value of KKN. Therefore, in order to manage development As the provision of clean water becomes more well planned, a database is needed that accommodates information regarding the availability of clean water in a location. Nagari atan Korong which can then be developed by Ekasakti University KKN-PPM Students 2024.